Это месть, детка! - Колычев Владимир Григорьевич (Лучшая криминальная драма, 2017)
Экземпляры: ф.7 (20170523) / Инвентарный номер: 53595 / Цена: 107.00 / Авт.знак: К 61 / ГРНТИ: 17.82.30 / ББК: 84(2Рос=Рус)6-44